ADR for consumers: an appraisal of the tribunal for consumer claims in Malaysia - Amin, Naemah; Abu Bakar, Elistina (Lexis Nexis, 2010)
A proper system of resolving consumer disputes is one of the most important components in consumer protection law. Since most consumer claims consists of small claims with low value, a redress system that is simple, cheap and instant is highly desirable. In this respect the ordinary court system is obviously unable to handle consumer claims effectively due to its high cost, time-consuming and formal procedures. Thus the establishment of the Tribunal for Consumer Claims in 1999 may be considered as a major landmark in the development of consumer protection law in Malaysia. The Tribunal has been in operation for merely ten years and has successfully settled thousands of consumer disputes. Despite its commendable performance, there are yet many improvements to be made. This paper seeks to examine the operation of the Tribunal for Consumer Claims and its effectiveness in providing informal, faster and cheaper procedures to consumers. The discussion focuses on the current deficiencies of the Tribunal and suggests any improvements for the benefit of the consumers. As a matter of comparison, the statutes of other countries relating to consumer tribunals are referred to which include the Consumer, Trader and Tenancy Tribunal Act 2001 (Act 82 of 2001) (New South Wales) (CTTT), the Commercial and Consumer Tribunal Act 2003 (No 30 of 2003) (Queensland) and the Disputes Tribunals Act 1988 (NO 110) (New Zealand).